2020
DOI: 10.1021/acs.jafc.0c03030
|View full text |Cite
|
Sign up to set email alerts
|

Kahweol Reduces Food Intake of Caenorhabditis elegans

Abstract: The coffee diterpene kahweol may contribute to the anti-obesity effects of coffee but its physiological effects have yet to be elucidated. Caenorhabditis elegans is used as an animal model in obesity research because its lipid metabolism is conserved in humans. The goal was to investigate kahweol’s effects on lipid metabolism in C. elegans. Kahweol at 120 μM reduced fat accumulation by 17% compared to the control, which was associated with a reduced food intake. Kahweol did not reduce fat in eat-2 mutants, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Nevertheless, Farias‐Pereira et al . (2020) found that the reduced fat accumulation by kahweol was associated with a reduced food intake, not the body size or energy expenditure in C. elegans . The differences might due to BPSs treatment started at the L1 stage, while kahweol treatment started at the adult stage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, Farias‐Pereira et al . (2020) found that the reduced fat accumulation by kahweol was associated with a reduced food intake, not the body size or energy expenditure in C. elegans . The differences might due to BPSs treatment started at the L1 stage, while kahweol treatment started at the adult stage.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, we assumed that BPSs after superfine grinding with better fat-lowering effects, mainly attributed to the changed structural characteristics of BPSs by superfine grinding. Nevertheless, Farias-Pereira et al (2020) found that the reduced fat accumulation by kahweol was associated with a reduced food intake, not the body size or energy expenditure in C. elegans. The differences might due to Ó 2024 Institute of Food, Science and Technology (IFSTTF).…”
Section: Effects Of Bps On Locomotive Activity Of C Elegans After Sup...mentioning
confidence: 85%
“…Dietary differences may be an important factor affecting tub‐1 levels. [ 43 ] The lipl‐4 gene encodes lipase, which maintains lipid homeostasis to prolong the life span of C. elegans . [ 44 ] The results showed that lipl‐4 was not modulated by OEB compared to the control, suggesting that the modulation of lipid metabolism by OEB might be independent of lipl‐4 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, kahweol did not play an important role until a threshold concentration was reached. Furthermore, the fat-lowering effects of kahweol were due to reduced food intake in C. elegans ( Farias-Pereira et al, 2020 ).…”
Section: Chemical Components In Coffee Tea and Cocoa As Preventative ...mentioning
confidence: 99%
“… Inhibited lipase activity in the small intestine by 56%; Significantly decrease TG and TC rates, and increase HDL-c level in serum Hamden et al (2013) In vitro , 3T3-L1 cells 75 and 100 μM Attenuates the adipocyte differentiation and lipid accumulation; Inhibits the expression PPARγ during adipogenesis Ilavenil et al (2014) In vivo , male C57BL/6J mice; In vitro , HepG2 cells 50 mg/kg, i.g. ; 25 and 50 μM Prevents high TC and hepatic lipid accumulation in mice, via restoration of hepatic autophagy Sharma et al (2018) In vitro , 3T3-L1 cells 10, 25, 50 and 75 μM Improves the lipid metabolism in adipocytes; Promotion of lipolysis and fatty acid oxidation, which induced the browning process of 3T3-L1 by activation β3-AR and inhibition PDE4 through MAPK/ATF-2 signaling Choi et al (2021) Kahweol In vitro , 3T3-L1 cells 5, 10 and 25 μg/mL Inhibited lipid accumulation; The expression levels of adipogenesis gene of PPARγ, C/EBPα, FABP4, FAS were reduced by activation the AMPK pathway Baek et al (2017) In vitro , 3T3-L1 cells 40 μM Inhibits adipogenesis in 3T3-L1 cells; Down-regulates the key adipogenic regulators of PPARγ and C/EBPα Kim et al (2018) In vivo , caenorhabditis elegans 30, 60, and 160 μM Reduced fat accumulation in wild-type C. elegans but not in eat-2 mutant, suggesting that fat-lowering effect depends on food intake Farias-Pereira et al (2020) Note: p.o. : per os; i.g.…”
Section: Introductionmentioning
confidence: 99%